Conservative treatment versus surgery in spondylotic cervical myelopathy: a prospective randomised study - Kadanka, Z; Bednarík, J; Vohánka, S; Vlach, O; Stejskal, L; Chaloupka, R; Filipovicová, D; Surelová, D; Adamová, B; Novotný, O; Nemec, M; Smrcka, V; et al. (European spine journal, 2000)
A prospective randomised 2-year study was performed to compare the conservative and operative treatment of mild and moderate forms of spondylotic cervical myelopathy (SCM). Forty-eight patients presenting with the clinical syndrome of SCM, with a modified Japanese Orthopaedic Association (mJOA) score of 12 points or more, were randomised into two groups. Group A, treated conservatively, consisted of 27 patients, mean age 55.6 +/- 8.6 years, while group B was treated surgically (21 patients, mean age 52.7 +/- 8.1 years). The clinical outcome was measured by the mJOA score, recovery rate (RR), timed 10 m walk, score of daily activities (recorded by video and evaluated by two observers blinded to the therapy), and by the subjective assessment of the patients at 6, 12, and 24 months of the follow-up. There was, on average, no significant deterioration in mJOA score, recovery ratio, or timed 10 m walk within either group during the 2 years of follow-up. In the surgery group there was a slight decline in the scores for daily activities and subjective evaluation. A comparison of the two groups showed no significant differences in changes over time in mJOA score or quantified gait, but there were significant differences in the score of daily activities recorded by video at 24 months, which was a little lower in the surgical group, and also in RR and subjective evaluation, which were both worse in the surgical group at months 12 and 24. However, at month 6, this last parameter was significantly better in the surgical than in conservative group. Surgical treatment of mild and moderate forms of SCM in the present study design, comprising the patients with no or very slow, insidious progression and a relatively long duration of symptoms, did not show better results than conservative treatment over the 2-year follow-up.
Keywords: výsledek terapie; tolerance zátěže; Disability Evaluation; Recovery of Function; komprese míchy; Male; Postoperative Complications; obnova funkce; progrese nemoci; Braces; posuzování pracovní neschopnosti; radiografie; Spinal Osteophytosis; osteofytóza páteře; Prospective Studies; mužské pohlaví; Disease Progression; pooperační komplikace; Cervical Vertebrae; Anti-Inflammatory Agents, Non-Steroidal; Treatment Outcome; antiflogistika nesteroidní; lidé; ženské pohlaví; Humans; Exercise Tolerance; Spinal Cord Compression; krční obratle; výztuhy; Female; lidé středního věku; Radiography; Middle Aged; prospektivní studie